Demographic variation in the injury patterns of adult cyclists admitted to a large US healthcare network: A five-year review. (July 2019) - Williams, Shanna E; Nelson, Rachel; Kashif, Reema; Goff, Tyler; Simon, Laura; Janse, Melissa
Background: Despite considerable health and environmental benefits, cycling is also associated with a risk of injury. Yet, variation in the patterns of cycling trauma which manifests by gender, age, and race/ethnicity is ill-defined. This retrospective study aims to characterize injury patterns in different demographic groups of bicyclists admitted to the Greenville Health System in South Carolina. Patients and methods: In this IRB-approved, retrospective study, five years of patient data (2010–2014) were gathered from seven emergency departments associated with the Greenville Health System. A total of 155 adult patients hospitalized for bicycle-related trauma were examined in terms of demographics (age, gender, and race) and injury. Injuries were categorized by type, region, and severity. Non-parametric tests were performed to study the effect of demographic characteristics on injury presentation. Results: Spinal cord ( p = 0.003) and internal organ injuries ( p = 0.000) were significantly more common in men. External body injuries were also more prevalent and severe in men ( p = 0.05), while injury to the extremities and pelvic region was more common and severe in women ( p = 0.02). Herniations ( p = 0.028), internal organ injuries ( p = 0.000), and abrasions ( p = 0.04) occurred more often in White cyclists. This group was also more likely to be wearing a helmet at the time of accident ( p = 0.00). Finally, while hematomas were more prevalent in older adults (≥55 years) cyclists ( p = 0.01), this population was also more also likely to wear a helmet than young adults (18–34 years) cyclists ( p = 0.025). Conclusion: Demographic differences exist in the types and severity of cycling trauma. These differences should be considered during the identification and management of bicycle-related trauma.